If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5=6n+5(-6n+1)
We move all terms to the left:
5-(6n+5(-6n+1))=0
We calculate terms in parentheses: -(6n+5(-6n+1)), so:We get rid of parentheses
6n+5(-6n+1)
We multiply parentheses
6n-30n+5
We add all the numbers together, and all the variables
-24n+5
Back to the equation:
-(-24n+5)
24n-5+5=0
We add all the numbers together, and all the variables
24n=0
n=0/24
n=0
| -8(-b-4)=-40 | | 1-20p+13p=-7p+7 | | 15w=7w+16 | | 2(x-2)(x+1)=20 | | 9-3(2x-4)=4(-3x+7)-2x | | 3k-8=1k= | | -2.75(s+-10)+-11.8=4.52 | | -6x=-5(x-1)+3x | | 17vv+27v+39=180 | | `8-0.25x=0.5x+2` | | 4-2c=-2c+4 | | 3y+4-y=14. | | −7/4v=−83/2 | | t+75=20 | | 4÷n+1=5 | | 68-9c=9c-4 | | 24/y=48 | | 4+3(2x+4)=-2-3x | | 2+5+b=9 | | 9-3(2x-4)=4(-3x7)-2x | | 8j=10−5(9j+2) | | 1/4x+2=15 | | -111=3(5x=3) | | 8=6+2qq= | | -9(x-7)=108 | | 3x+x-5=4x-2-3 | | –12=2+5v+2v | | 5p-9=-9+5p | | -3y+5.8=10 | | y/(-26)=23 | | –x+1=2 | | 4c-2c+1c+10=70 |